Spontaneous bilateral quadriceps tendon rupture: a case report - Onuoha, Kelechukwu Mc’Clement (Pan Afr Med J, 2020)
Quadriceps tendon rupture is an uncommon injury and mostly occurs among middle aged individuals that are involved in sports such as running or jumping. Spontaneous bilateral quadriceps tendon rupture is a rarer injury, however, can be debilitating. Patients with such injuries usually present with history of minor trauma, swelling and inability to actively extend the knee. Its occurrence secondary to minor trauma is mostly associated with chronic diseases and long-term use of certain medications. Occurrence of simultaneous bilateral quadriceps tendon rupture in the absence of trauma in a healthy patient with no known medical condition is yet to be reported and therefore requires a high index of suspicion for early diagnosis and effective management to avoid complications. The aim of this case report is to create awareness of the spontaneous occurrence of this injury in the absence of the reported risk factors. We report the unusual case of a 60-year old healthy man who presented with a spontaneous simultaneous bilateral quadriceps' tendon rupture in the absence of trauma and no medical risk factors. We report the unusual case of a 60-year old healthy man who presented with a spontaneous simultaneous bilateral quadriceps tendon rupture in the absence of trauma and no medical risk factors. Consent was taken from him to be used as a case report being a rare case. The man had full recovery after surgery and physiotherapy and was discharged home. Spontaneous bilateral quadriceps tendon rupture is a rare occurrence. The index case report is important as there was no history of trauma and it was bilateral.